Lactic acid bacteria : microbiological and functional aspects - Lahtinen, Sampo (CRC Press, 2012)
"Updated with the substantial progress made in lactic acid and bacteria research since the third edition, this fourth volume discusses improved insights in genetics and new molecular biological techniques. Thoroughly reorganized, this book incorporates the recent changes in new molecular techniques and the mechanistic understanding of probiotic functionality. The book remains firmly grounded in the basics of lactic acid bacteria; their genetics and taxonomy, their application in food and feed preparation, their health properties, and the legal issues associated with their use"--Anotace od vydavatele
Keywords: bakterie mléčného kvašení; laktobacily; Lactobacillus; potravinářská mikrobiologie; lactic acid bacteria; Lactobacillaceae; food microbiology; monografie; monographs